1995
DOI: 10.3109/00016489509139355
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Na, K-ATPase α and β Isoforms in the Neonatal Rat Cochlea

Abstract: The postnatal expression of five Na, K-ATPase alpha (alpha 1, alpha 2, alpha 3) and beta (beta 1, beta 2) subunit isoforms in the rat cochlea was investigated by immunocytochemistry. High levels of expression of the alpha 1 and beta 2 isoforms were observed in stria vascularis (SV) at all developmental stages. alpha 1 and beta 1 isoforms showed a distinct time-dependent developmental expression pattern in tissues of the spiral ligament (SL) and spiral limbus (SLi). Limited, temporary expression of alpha 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…However, immunohistochemistry studies have demonstrated that ATP1a1 and Kcnk1 are highly expressed in the marginal and vestibular dark cells. Both these proteins were shown at lower levels in the organ of Corti and spiral ganglion neurons (Zuo et al 1995;Nicolas et al 2003). We found higher levels of both these transcripts in the SG and OC compared with the LW, which does not appear to fit the protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunohistochemistry studies have demonstrated that ATP1a1 and Kcnk1 are highly expressed in the marginal and vestibular dark cells. Both these proteins were shown at lower levels in the organ of Corti and spiral ganglion neurons (Zuo et al 1995;Nicolas et al 2003). We found higher levels of both these transcripts in the SG and OC compared with the LW, which does not appear to fit the protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, earlier work also reported expression of the NKAα in the neuronal elements of the mammalian cochlea using a variety of techniques, including enzyme cytochemistry (Kerr et al 1982), in situ hybridization (Ryan and Watts 1991), and immunohistochemistry (Schulte and Adams 1989;Iwano et al 1990;McGuirt and Schulte 1994;Schulte and Steel 1994;ten Cate et al 1994;Nakazawa et al 1995;Zuo et al 1995;Erichsen et al 1996;Peters et al 2001;Weber et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Na-KATPase activity in the stria of the rat under goes a rapid increase between PNDs 12 and 18 [23] parallel to and probably responsible for the elevation in the magnitude of the endocochlear potential over the same period. The importance of Na-K-ATPasc activity for auditor)' transduction and amplification has been discussed above [24][25][26][27], Since the Na-K-ATPase isoforms found in the inner ear [54][55][56][57] are identical to those shown to be reg ulated in the neonatal brain by thyroid hor mone [49], it is very likely that the hormone regulates these isoforms in the ear also (ta ble 1). Additional evidence for the regulation of auditory development by thyroid hormone comes from the earlier onset of auditory activ ity in hormone injected neonatal rats [20,44], It is likely that thyroid hormone is also in volved in the regulation of the structural de velopment of the brain and the ear.…”
Section: The Thyroid Hormone Cascadementioning
confidence: 99%
“…These included spiral ligament (ai was first seen on PND 7, increased, reaching adult levels by PND 21; co began on PND 3, increased till PND 11 and then decreased by PND 14; p| w'as first apparent on PND 7 and reached adult levels by PND 14), stria vascu laris (ct| and P2 levels were elevated during all stages studied: co w'as first seen on PND 3 and increased till PND 11 and decreased by PND 14; Pi was initially apparent on PND 7 with low' levels thereafter), organ of Corti (ci| was first seen on PND 7 and increased to adult levels by PND 21:00 and P2 were seen initially on PND 7 with low' levels present thereafter: Pi levels were high from PND 7 into adult hood). inner hair cells, outer hair cells and cochlear nerve [54][55][56], Na-K-ATPase activi ty has been demonstrated by immunostaining in suprastrial fibrocytes(ci|, oo. pi subunit iso forms) and in strial marginal cells (ci|.…”
Section: The Thyroid Hormone Cascadementioning
confidence: 99%